The impact of a smoke-free policy on environmental tobacco smoke exposure in public housing developments - MacNaughton, Piers (Sci Total Environ, 2016)
BACKGROUND: Smoke-free housing policies have the potential to reduce secondhand smoke (SHS) exposures for residents of multi-unit housing. Since common areas represent a pathway of SHS movement between units, smoke-free policies would be expected to reduce SHS in these microenvironments. METHODS: Week-long air nicotine and PM(2.5) (particulate matter below 2.5 micrometers in aerodynamic diameter) samples were collected in the common areas of 10 Boston Housing Authority (BHA) and 6 Cambridge Housing Authority (CHA) buildings from January 2012 to October 2013. We also measured one outdoor PM level at each study building. Samples from BHA included pre and post- smoke-free policy measurements. Each development was visited three times over the course of the study period. The effect of the smoking ban on indoor PM(2.5) was examined using generalized mixed effect models to accommodate repeated measurement at each site. Changes in nicotine concentrations were modeled using quantile mixed regression to reduce the impact of outliers. RESULTS: After controlling for season, site, and background PM(2.5) concentrations, PM(2.5) levels were 4.05 µg/m(3) (p-value = 0.09) lower in BHA after the smoke-free policy was implemented in the summer of 2012, compared with CHA developments, which had no smoking policy in place. Similarly, nicotine levels decreased by 57% (p-value = 0.08) in Boston relative to Cambridge after the ban. CONCLUSIONS: Our findings support the use of smoke-free policies as an effective tool to reduce SHS exposure and protect non-smokers, especially residents of multi-unit housing.